Ambivalence about behavior change: utilizing motivational interviewing network of trainers' perspectives to operationalize the construct. (4th March 2017) - Rice, Samara L.; Hagler, Kylee J.; Martinez-Papponi, Brenda L.; Connors, Gerard J.; Delaney, Harold D.
Abstract: Motivational Interviewing (MI) is an empirically-supported approach for helping people change, but more research on its active ingredients and mechanisms of change is needed. One explanation, the conflict resolution hypothesis, states that it is MI's specific focus on exploring and resolving ambivalence – the simultaneous presence of both wanting and not wanting to change – that accounts for change. However, given that recognizing and appropriately responding to ambivalence is a central tenet of MI theory and practice, there has been little research on the conceptualization of ambivalence. In this study, 70 certified Motivational Interviewing Network of Trainers members responded to an online survey regarding: 1) the definition of ambivalence, 2) whether ambivalence was cognitive, emotional, or both, and 3) concepts that are often confused with, but are different from, ambivalence. Qualitative analysis of their responses revealed six related themes: 1) Coexistence of Opposites/Pros versus Cons Dynamic, 2) Emotions/Cognitions, 3) Behavioral Inertia, 4) Context of Ambivalence, 5) Factors Affecting Ambivalence, and 6) Cognitive versus Emotional Controversy. The second theme, Emotions/Cognitions, was further comprised of five subthemes: Conflict/Competition, Mixed Feeling or Thinking, Decision-making/Indecision, Desire, and Fear/Anxiety. The majority of respondents described ambivalence as both cognitive and emotional; the remainder supported either a primarily cognitive or emotional definition. Constructs that were commonly identified as being related to but distinct from ambivalence were resistance, denial, discrepancy, lack of motivation, and precontemplation/contemplation. These results highlight the apparent multifaceted nature of ambivalence. Ideally these findings also will be useful in the subsequent development of measures to assess ambivalence.